PENGARUH ICE BREAKING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMA 8 SUB TEMA 2 KELAS II SEKOLAH DASAR - Mery Selvia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2022)
This research is motivated by the low student learning outcomes in class II thematic learning. An effort to overcome these problems is to use Ice Breaking in thematic learning. This study aims to see the effect of applying Ice Breaking on thematic learning outcomes of second grade students of SD Negeri 21 Pulau Punjung. This study uses a True Experimental Design in the form of a posttest-only control design. The population in this study were all second grade students of SD Negeri 21 Pulau Punjung. The sample in this study was taken using systematic sampling. The data collection technique was carried out by giving a posttest in the form of a written test consisting of 17 multiple choice questions and 3 description questions. The results of the t-test analysis technique showed a significance level of 0.017 <0.05 so that H0 was rejected and Ha was accepted. This means that there is an effect of applying ice breaking to the thematic learning outcomes of second grade students of SD Negeri 21 Pulau Punjung, Dharmasraya Regency.